EOCENE LAGOMORPHA (MAMMALIA) OF ASIA: 2. STRENULAGUS AND GOBIOLAGUS (STRENULAGIDAE) - Lopatin A.V.; Averianov A.O. (My University, 2006)
Two species of early lagomorph, Strenulagus solaris sp. nov. (Monogolia, Khaychin-Ula 2 and 3 localities, Middle Eocene) and Gobiolagus hekkeri (Kyrgyzstan, Andarak 2 locality, terminal Lower Eocene), are described. A revision of Romanolagus hekkeri Shevyreva from the Andarak 2 locality has shown that it belongs to the genus Gobiolagus; consequently, the monotypic genus Romanolagus Shevyreva, 1995 is a junior synonym of Gobiolagus Burke, 1941. The diagnoses and species compositions of the genera Strenulagus and Gobiolagus are revised. Zaissanolagus gromovi Erbajeva from the Lower Oligocene of eastern Kazakhstan is shown to be the latest representative of the genus Gobiolagus and the family Strenulagidae. © Pleiades Publishing, Inc. 2006.
Keywords: ASIA; EOCENE; GOBIOLAGUS; LAGOMORPHA; STRENULAGIDAE; STRENULAGUS; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен